The South Wales Peer Review Group: A Case Study in Collaboration Part 2. (2nd October 2020) - Mhani, Nizar; Fowler, Peter; Lewis, Benjamin; Chandler, Carlen; Ulhaq, Aman; Smith, Christine; Williams, Julie; Abela, Stefan; Vithlani, Upen
Abstract : A two-part article is presented where a novel case study of how peer group collaboration, facilitated through digital technology, can be used to aid and facilitate the development of strategies for overcoming work-based challenges. Part 1 illustrated the importance of peer review in dentistry, introduced the inception of the South Wales Peer Review Group and explored the process of assembling the team of collaborators. Part 2 explains how the various considerations were assessed, how the collaborative ideas evolved and what outcomes were agreed. The topics for future discussion, necessary to overcome the challenges ahead, are also outlined. CPD/Clinical Relevance: During the COVID-19 pandemic, new strategies and protocols need to be developed to adhere to emerging and changing guidelines. The process of peer group collaboration is important for shaping the new service beyond the pandemic.